Características microbiológicas y organolépticas del salami aplicando nisina como conservante natural - Alcívar Alcívar, Gabriel Moisés (2018)
The objective of the research was to evaluate the effects of using Nisin as a natural preservative in the microbiological and organoleptic characteristics in salami and as a total substitute for nitrite. A DCA was applied with 4 treatments and three replicas, plus a control without application of this compound. The experimental unit was 5 kg per treatment. The percentages of Nisin used were 0.0025, 0.005, 0.0075, 0.010. The microbiological variables were evaluated: Salmonella, Clostridium perfringens and Staphylococcus aureus according to NTE INEN 1338-10. As a result, it was obtained that the best treatment was t4 with a Nisin dose of 0.010%, which complies with what is stipulated in the standard; Likewise, the organoleptic variable was measured using 75 untrained tasters, applying an ordination test against the control and the Friedman test; resulting with greater acceptability t4 treatment. It should be noted that this treatment was subjected to microbiological analyzes after one month to determine if Nisin was still acting and that there was contamination of Staphylococcus aureus based on what is established in the standard (NTE INEN 1338-10). It was possible to conclude that the use of Nisina is ideal in raw meat products matured but in doses equal to or greater than 0.010%.